Antiviral prophylaxis during pandemic influenza may increase drug resistance - Koch Daniel; Witschi Mark; Duerr Hans-Peter; Schwehm Markus; Eichner Martin; Brockmann Stefan O; Vidondo Beatriz (BMC Infectious Diseases, 2009)
Abstract Background Neuraminidase inhibitors (NI) and social distancing play a major role in plans to mitigate future influenza pandemics. Methods Using the freely available program InfluSim, the authors examine to what extent NI-treatment and prophylaxis promote the occurrence and transmission of a NI resistant strain. Results Under a basic reproduction number of R0 = 2.5, a NI resistant strain can only spread if its transmissibility (fitness) is at least 40% of the fitness of the drug-sensitive strain. Although NI drug resistance may emerge in treated patients in such a late state of their disease that passing on the newly developed resistant viruses is unlikely, resistant strains quickly become highly prevalent in the population if their fitness is high. Antiviral prophylaxis further increases the pressure on the drug-sensitive strain and favors the spread of resistant infections. The authors show scenarios where pre-exposure antiviral prophylaxis even increases the number of influenza cases and deaths. Conclusion If the fitness of a NI resistant pandemic strain is high, any use of prophylaxis may increase the number of hospitalizations and deaths in the population. The use of neuraminidase inhibitors should be restricted to the treatment of cases whereas prophylaxis should be reduced to an absolute minimum in that case.